Observações sobre a tradução de textos matemáticos cuneiformes - Gonçalves, Carlos H. B. [UNESP] (My University, 2011)
In this work, I deal with certain problems of translation that belong to cuneiform texts in general and more specifically to mathematical cuneiform texts. I analyse these problems from three points of view. Initially, I consider the intellectual mediations a cuneiform text undergoes until its translation. Next, I deal with the particularities of the concepts of the cuneiform mathematics, that is to say, its differences in relation to the mathematics of our time. Lastly, I treat aspects of the original languages of cuneiform texts that are still under discussion by the field. As a conclusion, I suggest that the results of this analysis are relevant not only to the translation process, but also to the reading of translations of mathematical cuneiform texts.
Remarks about the translation of mathematical cuneiform texts
Keywords: Akkadian; Cuneiform texts; Mathematics; Old babylonian period; Translation